Fluctuations in mHealth engagement following receipt of goal-discrepant feedback messages - Lex Hurley; Nisha G O’Shea; Brooke T Nezami; Carmina G Valle; Deborah F Tate (Digital Health)
Objective Digital behavior change interventions can successfully promote change in behavioral outcomes, but often suffer from steep decreases in engagement over time, which hampers their effectiveness. Providing feedback on goal performance is an established technique to promote goal attainment; however, theory indicates that sending goal-discrepant feedback messages could cause some users to respond more negatively than others. This analysis assessed whether goal-discrepant messaging was negatively associated with participant engagement, and if this relationship was exacerbated by baseline depressive symptoms within the context of a three-month weight loss pilot mHealth intervention. Methods This analysis applied a generalization of log-linear regression analysis with n  = 52 participants (78.8% female, 61.5% white, ages 21–35) to assess the likelihood of reading consecutive program messages following receipt of messages with goal-discrepant content. Results Receipt of goal-discrepant messages was associated with a significantly lower likelihood (RR = 0.89) of participants reading the next program message sent, compared to receiving positive/neutral messages or no message, but these relationships were not influenced by depressive symptoms in this sample. Conclusion Feedback on goal performance remains an important behavior change technique; however, sending push messages that alert participants to their goal-discrepant status seems to reduce the likelihood that participants will read future program messages. Sending messages containing positive or neutral content does not seem to carry this negative risk among individuals in goal-discrepant states.